(untitled) (INTEGRATION PROCEEDING, 2023)
Multinational corporations use many strategies to interest people about their product. One of the strategies is in the term of the language used. This study presents the use of code-mixing in Pizza Hut, as the target research. It used the ethnography study to describe the phenomenon of code-mixing. The qualitative research method is involved when the researcher gathered the data collection on how the code mixing used in Pizza Hut both on oral and written communication. Based on the data, the use of code mixing found in the term of interaction between waitress-costumers. While in written form, like menu and brochure, Pizza Hut consistently used code mixing with different frequency. In menu list, 80% used English and 20% used Bahasa Indonesia, while in brochure 50% use English and 50% used Bahasa Indonesia. The use of code mixing is a choice to persuade target buyer to interest and curious about the product which the multinational corporation offer.